Voice, power and legitimacy: the role of the legal person in river management in New Zealand, Chile and Australia. Issue 1 (2nd January 2019) - O'Donnell, Erin; Macpherson, Elizabeth
ABSTRACT: In 2017, rivers in New Zealand, India and Colombia received legal rights and were granted the status of legal persons. The increased legal powers, often a result of groundbreaking agreements or settlements with Indigenous peoples, may improve environmental protection and river management, but they can also challenge the legitimacy of laws and regulations that protect the rivers. In this paper, we compare the new legal rights with two long-standing uses of legal personality in river management, to explore the effects of legal personality in terms of environmental resource management. We argue that governments must ensure that they get the right balance between giving rivers a voice (and the power to be heard), and creating collaborative governance arrangements that strengthen and maintain community support overtime.